Age-related Trends in Adults with Urinary Tract Infections Presenting to the Emergency Department: A 5-Year Experience - Cardone, Silvia; Petruzziello, Carmine; Migneco, Alessio; Fiori, Barbara; Spanu, Teresa; D'Inzeo, Tiziana; Franceschi, Francesco; Ojetti, Veronica (Reviews on Recent Clinical Trials, 2019)
Introduction: Urinary tract infections (UTIs) are among the most common bacterial infections, affecting 150 million people worldwide each year. Importantly, the incidence of UTI increases markedly with age. The increasing resistance to empirically prescribed antimicrobial agents complicates the management of this disease. This makes UTI an important issue in increasingly aging population and updated epidemiological investigation is advisable. To understand the epidemiological variation in UTI resistance patterns among differently aged populations, we conducted a retrospective study among patients presenting to the emergency department (ED) of a large tertiary-care hospital in Italy during January 2013 and June 2017. Methods: 1281 patients who presented with UTI symptoms to the ED, were stratified into four age categories: young adults (18-44 years old;), adults (45-64), the elderly (65-84), and the oldest old (≥ 85). Inclusion criteria were urine collected in ED patients with UTI symptoms and first positive culture from one given patient in a given year. Results: 362 (28.2%) patients had a urine culture with positive result, leading to a total of 459 germs isolated, stratified into four categories: young adults (58 isolates, 12.6%), adults (98, 21.4%), the elderly (174, 37.9%), and the oldest old (129, 28.1%). Escherichia coli represents the 60% of all monomicrobial infections, followed in frequency by Klebsiella pneumoniae (15%), and Enterococcus faecalis (5%). The other 20% of the infections are caused by various germs. The most common association of germs in polymicrobial is E. coli + E. faecalis, accounting for the 28% of all infections. Overall, we found a peak of susceptibility to amoxicillin (AMX) in the oldest old ( 81%), significantly higher compared to young adults (54%), adults (47%) and elderly (35%) (p<0,001). For ciprofloxacin (CIP) there is a greater susceptibility in the young adult (55.5%), but not so marked compared to the other three groups; for fosfomicin (FOS) the susceptibility was greater in the group of adults (60%) compared to young adults, elderly and the oldest old. Also for trimethoprim/ sulfamethoxazole (TMP-SMX) we found greater susceptibility in the adult group (60%), followed by the oldest old (57,6%), young adults (49%) and elderly (47%). Conclusion: Age-related differences in antimicrobial-resistant microorganisms were evident for adults with UTI, and could potentially contribute to the risk of inappropriate empirical therapy in elderly patients. Thus, different empirical antimicrobial regimens should be considered for distinct age groups.
Keywords: Antibiotic resistance